The value of 'having a go': Trialing a project-based learning activity to inform curriculum design. Issue 4 (2nd October 2018) - Stokes, Alison; Harmer, Nichola
Abstract: Active, student-centered pedagogies such as project-based learning (PjBL) can offer significant potential for engaging undergraduates with complex sustainability issues. Driven by institution-wide curriculum changes and informed by educational theories and evidence from previous studies, a trial PjBL activity was designed and delivered on three separate occasions, to three different student groups, at a university in the United Kingdom. In these trials, students from geography, Earth, and environmental science (GEES) programs worked in small (5 to 6 people), multiple-discipline teams to explore a single research question focused on a global sustainability issue. The perceptions and experiences of the trial participants (students and faculty) were investigated using data from surveys and interviews, and the findings applied to designing a new, multiple-disciplinary module focused on energy and climate change. In general, all participants engaged positively with the PjBL approach, although issues around the nature and extent of support available to the students and appropriate methods of assessing PjBL outputs emerged as requiring further consideration. The findings demonstrate that a single research question need not constrain the approach students take when completing a PjBL activity and identify clear potential benefits in terms of developing students' wider professional skills. This study also highlights the value to curriculum developers in trialing new pedagogic approaches, as the opportunity to "have a go" enabled potential issues for learners and instructors to be identified and mitigated prior to the final module design and implementation.